HCV treatment access among Latinxs who inject drugs: qualitative findings from Boston, Massachusetts, 2016 - Avni Mittal; Karen C. Kosinski; Thomas J. Stopka (BMC, 2019)
Abstract Background Compared with Caucasians, Latinxs with the hepatitis C virus (HCV) tend to initiate treatment less often, discontinue treatment, become infected younger, and have higher reinfection rates post-treatment. Little is known about HCV treatment experiences among Latinxs who inject drugs in the Northeastern USA. We assessed knowledge, attitudes, and perceptions tied to HCV, as well as HCV treatment readiness, and explored the overall HCV treatment experience of Latinx people who inject drugs (PWID) in Boston. Methods We conducted qualitative interviews with monolingual and bilingual Spanish-speaking Latinx PWID (n = 15) in Boston, Massachusetts, between 2015 and 2016. We used a thematic content analysis approach to code and analyze data to identify knowledge, attitudes, and experiences related to HCV treatment. Results We identified barriers and facilitators to HCV treatment. Six salient themes emerged from the data. For participants who had not initiated HCV treatment, lack of referral, fear of quitting drugs, and fear of relapse were perceived barriers. Trust in medical providers and a willingness to quit drugs were primary facilitators. Most participants had positive HCV treatment experiences, and several emphasized the need for outreach to Latinxs about the advantages of newer treatment options. Concerns about HCV reinfection were also notable. Conclusions We identified a range of experiences tied to HCV treatment among Latinx PWID. HCV care providers play a key role in determining treatment uptake, and more treatment information should be disseminated to Latinx PWID. Healthcare providers should capitalize on treatment facilitators by ensuring referrals to treatment and should continue to address perceived barriers.